Surface Coating of Hastelloy C 276 by WS2 Added Meso-electrical Discharge Alloying Process - Dutta, Souradeep; Sarma, Deba Kumar; Dutta, Hrishikesh (Journal of materials engineering and performance, 2025)
The current research optimizes the coating parameters which resulted a solid lubricating hard, wear-resistant layer over the surface of Hastelloy C 276 through WS 2 powder added meso-electrical discharge alloying process. It investigates the impact of process characteristics i.e., gap voltage ( V a ), pulse on time ( t on ), and WS 2 powder concentration ( P c ) on the material deposition rate (MDR), surface roughness ( R a ), and hardness of the modified surface. The rise in V a and t on increases the MDR, R a and hardness, whereas the surge in P c increases the MDR, reduces the R a and enhances the hardness of the coated surface. The proposed hybrid optimization method gray relational-based genetic algorithm (GRGA) raises the MDR and hardness by 16.15 and 11.89%, respectively, and reduces the R a by 15.71% compared to the gray relational analysis method. No noticeable micro-voids and micro-cracks were obtained at the optimal GRGA condition. Energy-dispersive x-ray spectroscopy and x-ray diffraction analysis at GRGA conditions verify the presence of different elements and hard phases like MoO 2 , ZnO, WC and WO 3 on the alloyed surface. The coated surface at the GRGA optimum setting has the lowest specific wear rate as compared to the HC 276 substrate.